The Influence of Coaches’ Leading Behavior on Young Athletes’ Psychological Pressure and Psychological Adaptation - Yansen Li; Yulin Yang; Jing Yu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This study investigates the relationship between psychological strain, psychological adaptation, and coaches in young athletes. Using athletes and coaches from various local and provincial diving teams and among these, training dimensionality changes in the N-dimensional low group were significantly greater in the low and middle groups than in the middle and high groups. N-dimensional changes were significantly less in the low and middle groups than in the middle and high groups. There is a significant difference between athletes in the N-dimensional low group and those in the intermediate group on the social support dimension. The E-dimension high and low groupings, the changing pattern of movement, and the association between education and autocratic conduct vary significantly. When coaches enhance their social support behaviours, they can compensate for external problems such as losing satisfaction with the athlete's training game. For the low E-dimension group, the association between exercise and education is poorer if the authoritarian behavior is high. For the high E-dimension group, if the authoritarian conduct is high, the relationship between exercise and education is better.